Why and how should we simulate platform trials? Learnings from EU-PEARL - Elias Laurin Meyer; Tobias Mielke; Marta Bofill Roig; Michaela Maria Freitag; Peter Jacko; Pavla Krotka; Peter Mesenbrink; Tom Parke; Sonja Zehetmayer; Dario Zocholl; Franz König (BMC Medical Research Methodology)
Abstract Background Platform trials are innovative clinical trials governed by a master protocol that allows for the evaluation of multiple investigational treatments that enter and leave the trial over time. Interest in platform trials has been steadily increasing over the last decade. Due to their highly adaptive nature, platform trials provide sufficient flexibility to customize important trial design aspects to the requirements of both the specific disease under investigation and the different stakeholders. The flexibility of platform trials, however, comes with complexities when designing such trials. In the past, we reviewed existing software for simulating clinical trials and found that none of them were suitable for simulating platform trials as they do not accommodate the design features and flexibility inherent to platform trials, such as staggered entry of treatments over time. Results We argued that simulation studies are crucial for the design of efficient platform trials. We developed and proposed an iterative, simulation-guided “vanilla and sprinkles” framework, i.e. from a basic to a more complex design, for designing platform trials. We addressed the functionality limitations of existing software as well as the unavailability of the coding therein by developing a suite of open-source software to use in simulating platform trials based on the R programming language. To give some examples, the newly developed software supports simulating staggered entry of treatments throughout the trial, choosing different options for control data sharing, specifying different platform stopping rules and platform-level operating characteristics. The software we developed is available through open-source licensing to enable users to access and modify the code. The separate use of two of these software packages to implement the same platform design by independent teams obtained the same results. Conclusion We provide a framework, as well as open-source software for the design and simulation of platform trials. The software tools provide the flexibility necessary to capture the complexity of platform trials.